2018
DOI: 10.1186/s12958-018-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Omega-3 fatty acid for polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: ObjectiveTo assess the effectiveness and safety of omega-3 fatty acid for patients with PCOS.MethodsIn this meta-analysis, data from randomized controlled trials were obtained to assess the effects of omega-3 fatty acid versus placebo or western medicine in women with PCOS. The study’s registration number is CRD42017065859. The primary outcomes included the change of homeostatic model assessment (HOMA) of insulin resistance, total cholesterol (TC), triglyceride (TG) and adiponectin.ResultNine trials involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 37 publications
1
52
1
2
Order By: Relevance
“…Studies on PCOS women have shown the ability of some dietary factors like anti-inflammatory materials to improve the metabolic disorder of patients [5,23]. Women with PCOS have demonstrated a higher level of inflammatory mediators such as tumor necrosis factor, C-reactive protein, and tissue plasminogen activator in their blood which is associated with insulin resistance [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on PCOS women have shown the ability of some dietary factors like anti-inflammatory materials to improve the metabolic disorder of patients [5,23]. Women with PCOS have demonstrated a higher level of inflammatory mediators such as tumor necrosis factor, C-reactive protein, and tissue plasminogen activator in their blood which is associated with insulin resistance [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some studies indicate that certain nutrition and dietary factors can decrease symptoms of the PCOS. Based on Yang et al's study in 2018, omega-3 fatty acid may be recommended for the treatment of PCOS in women with high insulin resistance as well as high cholesterol and triglyceride [5]. Other studies have indicated that herbal medicines especially herbs with anti-inflammatory effects can also be effective [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…n-3 Fatty acid supplementation in type 2 diabetes mellitus patients caused a significant improvement in TAG, VLDL-cholesterol and LDLcholesterol levels (9) . In some studies, n-3 fatty acid supplementation in patients with non-alcoholic fatty liver disease (28) and polycystic ovary syndrome (29) decreased plasma TAG levels. However, in contrast to our findings, Jovanovski et al (10) indicated that ALA did not affect glycaemic control.…”
Section: Effects On Glycaemic Control and Lipidsmentioning
confidence: 99%
“…Previously, the importance of FA profiles in AT of pregnant women and mothers has been shown by researchers from France [9], Poland [10], and Portugal [11], which warrants further studies in developing countries such as Iran. On the other hand, it has been suggested that FAs are associated with the risk of a wide range of chronic diseases such as PCOS [12,13]. In this regard, trans-FA (TFA) and saturated FA (SFA) are reported to play significant roles in the development of several disorders through their stimulating action and n-3 polyunsaturated fatty acids (PUFA) contribute by their suppressive action [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been suggested that FAs are associated with the risk of a wide range of chronic diseases such as PCOS [12,13]. In this regard, trans-FA (TFA) and saturated FA (SFA) are reported to play significant roles in the development of several disorders through their stimulating action and n-3 polyunsaturated fatty acids (PUFA) contribute by their suppressive action [11,[13][14][15]. The increased amounts of linoleic acid (LA; C18:2 n-6) by 136% in the AT over the last half century in the United States [16], and the increase in the dietary n-6:n-3 FA ratio from 1:1 to 20:1 [17], point to their possible roles in chronic diseases such as PCOS.…”
Section: Introductionmentioning
confidence: 99%